2022
DOI: 10.1371/journal.pone.0274887
|View full text |Cite
|
Sign up to set email alerts
|

Differences in risk factors for surgical site infection between laparotomy and laparoscopy in gastrointestinal surgery

Abstract: Extensive gastrointestinal surgery surveillance data in Japan were analyzed to examine the differences in the risk factors for surgical site infection (SSI) between laparotomy and laparoscopic abdominal procedures. Surgical procedures investigated in the study were gastrectomy, cholecystectomy, colectomy, rectal resection, and appendectomy. A total of 32,629 patients were included in the study. The study participants were divided into two groups according to the year of surgery, 2003–2009 (first study period) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Among the surgical operation factors, our review showed that operation time ≥3 h, laparotomy operation and blood transfusion significantly increased the risk of SSI in patients with gastric cancer. In our study, we found that operation time ≥3 h and laparotomy could increase the risk of SSI in gastric cancer patients by 8.33 times and 2.18 times, respectively, which was consistent with previous studies 46‐48 . Operation time was considered to reflect complexity of the surgery 49 and it could increase the risk of SSI in gastric cancer patients by 1.52 times 48 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the surgical operation factors, our review showed that operation time ≥3 h, laparotomy operation and blood transfusion significantly increased the risk of SSI in patients with gastric cancer. In our study, we found that operation time ≥3 h and laparotomy could increase the risk of SSI in gastric cancer patients by 8.33 times and 2.18 times, respectively, which was consistent with previous studies 46‐48 . Operation time was considered to reflect complexity of the surgery 49 and it could increase the risk of SSI in gastric cancer patients by 1.52 times 48 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found that operation time ≥3 h and laparotomy could increase the risk of SSI in gastric cancer patients by 8.33 times and 2.18 times, respectively, which was consistent with previous studies. [46][47][48] Operation time was considered to reflect complexity of the surgery 49 and it could increase the risk of SSI in gastric cancer patients by 1.52 times. 48 Inokuchi et al also found that laparotomy surgery was associated with a significantly higher incidence of SSI than laparoscopic surgery, the former could increase the risk of SSI in gastric cancer patients by 0.5 times.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports comparing the safety of open cholecystectomy with that of laparoscopic cholecystectomy in patients with CSF shunts. Open cholecystectomy is more invasive and associated with a higher risk for surgical site infection compared to laparoscopic cholecystectomy 36,37 . Compared to laparoscopic cholecystectomy, more invasive surgeries, such as gastrectomy and colorectal surgery can be performed without shunt intervention if uncontaminated 23–27 .…”
Section: Discussionmentioning
confidence: 99%
“…Open cholecystectomy is more invasive and associated with a higher risk for surgical site infection compared to laparoscopic cholecystectomy. 36,37 Compared to laparoscopic cholecystectomy, more invasive surgeries, such as gastrectomy and colorectal surgery can be performed without shunt intervention if uncontaminated. [23][24][25][26][27] Therefore, shunt intervention may not be necessary as long as the surgical field is uncontaminated, even if inflammation is severe and open or conversion to open cholecystectomy is needed.…”
Section: Analysis Of Perioperative Shunt Managementmentioning
confidence: 99%
“…Open laparotomy with gastroenterological surgery is a surgical procedure that is performed with a cleancontaminated wound by wound classi cation [1,2]. Thus, it often results in a relatively high rate (about 10% or more) of incisional SSI [3,4,5].…”
Section: Introductionmentioning
confidence: 99%